The effects of spray atomization by using blended alumina oxide, titanium oxide, and cerium oxide nano particles with diesel fuel in direct injection engine - Ali Mohammed Omar Salem, Ba Saleem (2023)
Various studies have been undertaken over the previous decades to locate an alternative fuel that can reduce the environmental issues caused by diesel fuel. A previous study has indicated nano-enhanced diesel fuels as viable diesel fuel alternatives. However, research on nano-enhanced diesel fuel's physical properties and spray characteristics is sparse. The goal of this study was to look at the macroscopic spray parameters like spray penetration length and cone angle of different nano diesel fuels like DFAL (alumina diesel fuel), DFTI (Titanium diesel fuel), and DFCE (cerium diesel fuel) at concentrations of 25, 50, and 75 parts per million (ppm). The spray properties were explored using a high-speed camera in continuous static situations by shadowgraph methods. Experiments were carried out at room temperature using 50, 80, and 100 MPa injection pressures. The images of the test fuels are handled with the picture editing programs da-Vinci and ImageJ.Ultrasonic vibration served as the experiment's stabilizing approach. Furthermore, the peak absorbance of the nanofluid, the connection between concentration and absorbance, the optimal sonication period, and time-dependent sedimentation data were used to study fuel stability. All three doses' absorbances declined when compared to their original absorbances but remained more than 80% stable over 200 hours. Fixing the concentration at 25 ppm while varying the pressure shows that a better dispersion occurs due to the increase of the power of the injector, therefore, better spray tip penetration (STP), and spray cone angle (SCA), for example, DFTI initial distance increased by 30% at 27.25 mm in 0.1 ms and breakup time of 0.3 ms faster than the neat diesel D100 at 80 MPa. They were followed by DFAL and DFCE at break up time of 0.4 ms at a distance of 26.51 mm and 44.3 mm from 0.1 ms. In terms of increasing concentration, it can be summarized that increasing nanoparticles aids the perdormance of the atomization process; however, reaching higher concentrations, such as 100 ppm, is not a suitable approach because it affects the physical properties of the fuel, which reflect on cerium nanoparticle DFCE, which achieves poor values compared to where using 50 ppm nano concentration at all injection pressures of 50,80, and 100 MPa are sufficient to allow the fuel to atomize. To summarize, increasing pressure increased the interaction of the nano fuel with the surrounding environment, resulting in more penetration than pure diesel due to improved spray dispersion.Regarding cone angle, the nano fuel is identical to the neat but has superior penetration.Furthermore, Findings indicate that increasing injection pressure leads to greater penetration. While lowering breakup time, which was greater with the nano-enhanced fuel. The fuel blend was better and atomized faster than the neat diesel, which took too long to reach the edge of the wall. As a result, the fuel did not atomize equally, leading the diesel to enter too slowly and the angle to rise drastically. When using the split injection method, raising the pressure substantially influenced the macroscopic aspects of the spray. Higher pressure of the injected fuel in general increased the interaction of the nano fuel with the surrounding environment, resulting in greater penetration compared to neat diesel due to improved spray dispersion.